The Development of Turtle Trek: Sea Turtle Odyssey - Ng, Gu Feng; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2024)
“Turtle Trek: Sea Turtle Odyssey” is a 2D side-scrolling mobile game designed to raise awareness about sea turtle conservation by engaging users with an interactive and educational experience. Through comprehensive testing, the game demonstrated high functionality and usability, achieving an average System Usability Scale (SUS) score of 71.63, which indicates an acceptable level of user satisfaction. The game successfully educated players about the life stages of sea turtles and the threats they face, combining entertainment with valuable learning outcomes. User feedback confirmed the game’s effectiveness in meeting its objectives, highlighting strengths such as its immersive learning experience, educational impact, and diverse multimedia elements. However, areas for improvement include addressing potential gameplay repetition, expanding language options, and adding advanced features like multiplayer modes. Overall, “Turtle Trek: Sea Turtle Odyssey” proved to be a successful tool for promoting environmental awareness and conservation efforts, suggesting a good place for similar educational initiatives in the future.